Tinjauan Fiqh ‘Urf Terhadap Praktik Perjanjian Perkawinan (Studi Empiris Adat Dayak Ngajudi Kota Palangka Raya) - Nurulia Shalehatun Nisa (HKI IAI Miftahul Ulum Pamekasan, 2022)
Marriage agreements in Indonesia are regulated in the Civil Code (KUHPerdata), Compilation of Islamic Law (KHI), and Law Number 1 of 1974 concerning Marriage (Marriage Law) jo. Decision of the Constitutional Court Number 69/PUU-XIII/2015 so that the marriage agreement is legal and lawful. The marriage agreement in the Dayak Ngaju indigenous people is called a symbol. Perlambang is one of a series of traditional Dayak Ngaju marriage procedures. This paper aims to analyze the practice of marriage agreements that grow and live to become a culture of the Dayak Ngaju indigenous people in Palangka Raya City when viewed from the point of view of 'Urf. This writing is the result of research qualitative or empirical studies.The marriage agreement made to the Ngaju Dayak indigenous people has an important role, even though it is part of a series of traditional marriage rituals which in fact originates from the Hindu Kaharingan religion, but in its journey along with the introduction of Islam among the people, it has experienced various adaptations and adjustments to Islamic beliefs. . So that in practice, marriage agreements in the Dayak Ngaju customary community can still be carried out and benefited even by people who are Muslim.